Bicuspid Aortic Valve Disease: A Comprehensive Review - Ify Mordi; Nikolaos Tzemos (Cardiology Research and Practice)
Bicuspid aortic valve is the commonest congenital cardiac abnormality in the general population. This paper article will discuss our current knowledge of the anatomy, pathophysiology, genetics, and clinical aspects of bicuspid aortic valve disease.